New Acridone Inhibitors of Human Herpes Virus Replication - Bastow, K. F. (Current Drug Targets - Infectious Disorders, 2004)
Modern biomedicinal research with acridones began with plant secondary metabolites but the successful development of these alkaloids into drugs has yet to be realized. However, there are synthetic acridones unrelated to the natural products now emerging as promising bioactive compounds. The purpose of this mini-review is to highlight the renewed interest in acridones for antiviral drug research, with the emphasis placed on several derivatives in early stage development for treating herpes virus infection. Novel anti-herpes acridones developed using a ligand-based approach have much simpler structure and generally have higher selectivity than the corresponding alkaloids. Three sub-types are currently classified on the basis of activity against Herpes Simplex Virus (HSV) and, or Human Cytomegalovirus (HCMV) and all of them inhibit viral replication postadsorption. In terms of mode / mechanism of action, this “second wave” of early generation lead molecules appears unique in comparison to the natural products and to drugs derived from more traditional templates. Inhibition of HSV replication by these agents is best understood and it occurs after viral DNA synthesis. The mechanism for one prototype inhibitor (5- chloro-1,3-dihydroxy acridone), involves a blockade of viral DNA maturation (cleavage / packaging) and viral capsids accumulate abnormally. Interestingly, the 7-Chloro regioisomer blocks a later stage of viral assembly. At this time it is unclear whether atypical target-interaction or unusual polypharmacology is responsible for the antiviral activities observed and this key issue will hamper future drug development until it is resolved.
Keywords: cytomegalovirus